The differences of the oral hygiene status in patients with cleft lip and palate pre operative and post operative in Takalar Regency - Muhammad I. Rasul; Andi Tajrin; Muhammad Ruslin; Abul Fauzi; Kumiko Fujiwara; Makoto Noguchi; Sitti NW. Al-Bashir (DiscoverSys Inc., 2020)
Objective: This study aims to determine the difference in oral hygiene status in patients with cleft lip and palate pre operative and post operative in takalar regency. The sample in this study were patients with cleft lip and palate preoperative and postoperative with a total sample of 20 people consisting of 10 people for the preoperative group and 10 people for the postoperative group.Material and Methods: This study is observational analytic and the design of this study is Cross Sectional Study. Determination of samples was done by quota sampling. Assessment of oral hygiene status was obtained from OHI-S scores. The data obtained were tested with chi-square test and t-test by SPSS.Results: In the group of patients with cleft lip and palate preoperative had an average oral hygiene status of 2.69 while the postoperative group was 2.04 with p-value of 0.062 (> 0.05). Conclusion: There was no difference in the status of oral hygiene in patients with cleft lip and palate preoperative and postoperative in Takalar regency.